Strategies of high performing new and small firms: A reexamination of the niche concept - Cooper, Arnold C.; Willard, Gary E.; Woo, Carolyn Y. (Journal of Business Venturing, 1986)
Entrepreneurs seeking to position new or small firms in industries populated by well established competitors are frequently advised to seek the protection of a market niche. There, shielded by market characteristics which render the niche uninteresting to larger rivals, small firms are urged to compete at the fringe of the market. This article challenges this conventional wisdom, citing industry and firm characteristics which, under certain conditions, create opportunities for successful direct competition by some small or new firms against much larger and established competitors. However, the authors caution that the conditions which created the opportunity may erode in time, rendering the successful challenger vulnerable either to retaliation by the larger firm or challenge from subsequent entrants. Examples of successful direct confrontation by relatively small competitors are drawn from mature, low-tech industries, a rapidly growing high-tech industry and the service sector.